Condition of Soil Fertility and Sensory Profile of Smallholder Robusta Coffee in Jember District - Niken Puspita sari; Dwi Nugroho (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Jember district is one of the centers for smallholder plantation of the Robusta coffee in East Java. However, there are still limited reports about environmental conditions, particularly soil fertility of existing smallholder plantations and its effect on coffee flavor. The purpose of this study was to investigate the effect of soil fertility on flavor of coffee in existing smallholder Robusta coffee plantations in Jember district. This research was carried out by survey method in several area of the smallholder Robusta coffee plantation in Jember. Evaluation of sensory profile was carried out using cup test organoleptic method based on Standard cupping method of the Specialty Coffee Association of America. Research locations as subdistricts were chosen by purposive sampling method, namely Panti, Silo, Rambipuji, Sukorambi, and Tanggul subdistricts. Results of this study showed that soil of the smallholder Robusta coffee plantation in research locations possessed low organic carbon content in Sukorambi subdistrict and medium concentration in other locations. Nitrogen content was low in all locations, potassium in Sumber Baru subdistrict was high whereas other locations were medium. Phosphorus availability was high in all locations. Calcium and magnesium were medium in Panti, Sukorambi, Sumber Baru, and Silo subdistricts. Soil acidity was low in all locations. Results of the sensory analysis of smallholder’s Robusta coffee was from divided into three groups. First, categorized as fine Robusta coffee was smallholder’s Robusta coffee samples obtained from Silo and Sukorambi subdistricts. Second, good quality Robusta coffee was from smallholder Robusta coffee samples from Panti and Sumber Baru subdistricts. Third, medium quality Robusta coffee was from smallholder’s Robusta coffee from Tanggul subdistrict. Total scores of coffee testing from samples of Panti, Sukorambi, Sumber Baru, Tanggul, and Silo subdistrict were 79.8, 82.0, 79.9, 76.0, and 82.5, respectively